2020
DOI: 10.1002/ajum.12202
|View full text |Cite
|
Sign up to set email alerts
|

Do radiologists need to review abdominal ultrasound examinations reported as ‘normal’ by the sonographer?

Abstract: Introduction Sonographers demonstrate a high standard of diagnostic performance and work with a considerable degree of professional independence. In Australasia, sonographers typically generate a preliminary report which is reviewed by the radiologist who issues a final report. The aim of this study was to determine whether radiologist's review is required in cases reported as normal by the sonographer. Methods This study was a retrospective review of 1000 abdominal US examinations considered normal by sonogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 18 publications
(19 reference statements)
1
17
0
Order By: Relevance
“…Sonographers do not generate final reports in Australia but contribute significantly by providing evidence, such as sonographer worksheets and still images, which form the report. 27,28 Some sonographers view this mechanism as an opportunity ‘to have a second set of eyes look at things’ (PS17). For others, this only increases the points at which errors in reporting could occur due to breakdown or misinterpretation in communication in translating findings from a dynamic scan via static modes of communication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sonographers do not generate final reports in Australia but contribute significantly by providing evidence, such as sonographer worksheets and still images, which form the report. 27,28 Some sonographers view this mechanism as an opportunity ‘to have a second set of eyes look at things’ (PS17). For others, this only increases the points at which errors in reporting could occur due to breakdown or misinterpretation in communication in translating findings from a dynamic scan via static modes of communication.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show close correlation between sonographer findings and reports. 29,28 However, evidence has shown that sonographers tend to use disclaimers regarding image quality, which presents uncertainty in sonographers’ findings from their worksheets. 29 Errors in radiological diagnosis can arise at different phases, including acquisition of images, interpretation of findings as well as missed diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Sonographers are highly accurate diagnosticians whose diagnostic performance in US has been shown to be on a par with that of radiologists in a number of studies. [23][24][25][26][27][28][29][30] There is therefore no reason to suspect that under the additional pressure of a pandemic, the sonographer's diagnostic performance would somehow become compromised.…”
Section: Discussionmentioning
confidence: 99%
“…Sonographers demonstrate a high standard of diagnostic performance and work with a considerable degree of professional independence 1 . The high accuracy of sonographers' diagnostic opinion has been documented in numerous studies across all subspecialties with sonographers demonstrating comparable diagnostic performance to radiologists 2–15 . A recent large study involving 1000 abdominal ultrasound (US) examinations reported as ‘normal’ by sonographers, demonstrated that sonographers have near perfect accuracy in distinguishing a normal examination and commit the same number of reporting errors as radiologists 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The high accuracy of sonographers' diagnostic opinion has been documented in numerous studies across all subspecialties with sonographers demonstrating comparable diagnostic performance to radiologists 2–15 . A recent large study involving 1000 abdominal ultrasound (US) examinations reported as ‘normal’ by sonographers, demonstrated that sonographers have near perfect accuracy in distinguishing a normal examination and commit the same number of reporting errors as radiologists 15 . The aim of this study was to compare the abnormal US findings independently reported by sonographers with the final reports issued by radiologists in the complex working environment of a large tertiary teaching hospital.…”
Section: Introductionmentioning
confidence: 99%